2010
DOI: 10.1186/1749-8090-5-57
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin as a possible new treatment option for surgical management of Methicillin-Resistant Staphylococcus aureus sternal wound infection after cardiac surgery

Abstract: We present a case of a 77-year old female who had undergone a coronary artery bypass grafting with an aortic valve replacement and developed three month later a Methicillin-Resistant Staphylococcus aureus (MRSA) sternal wound infection which was successful treated with Daptomycin combined with vacuum-assisted closure (VAC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…Interestingly, data on the optimal antibiotic management or duration of therapy for DSWI is scarce. Daptomycin has shown to be effective combined with multiple surgeries for treatment of DSWI in cardiac surgery [1,3,4]. However, up till now, no study has shown midterm results in terms of re-infection or re-operation for patients who were successfully treated with daptomycin for gram-positive DSWI.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, data on the optimal antibiotic management or duration of therapy for DSWI is scarce. Daptomycin has shown to be effective combined with multiple surgeries for treatment of DSWI in cardiac surgery [1,3,4]. However, up till now, no study has shown midterm results in terms of re-infection or re-operation for patients who were successfully treated with daptomycin for gram-positive DSWI.…”
Section: Resultsmentioning
confidence: 99%
“…For these highly specific infections Daptomycin has proved to be an effective treatment [1,4,5]. To prevent prolonged hospitalisation and need for device exchange, we recommend an aggressive antibiotic therapy with Daptomycin combined with local debridement and vacuum treatment in infected wound cavities.…”
Section: Discussionmentioning
confidence: 99%
“…Как известно, стафилококк является наиболее распространенным патогеном, выделяемым при инфекциях кожи и мягких тканей, который нередко демонстрирует резистентность к антибиотикам широкого спектра и требует длительной антибактериальной терапии. Даптомицин, первый антибиотик из класса циклических липопептидов, обладает доказанной эффективностью при лечении бактериемий и инфекционных осложнений в кардиохирургии, включая эндокардиты, обусловленные метициллинрезистентными штаммами стафилококков [15,16]. В связи с большей (в сравнении с ванкомицином) пенетрацией препарата в костную и периартикулярные ткани терапия даптомицином успешна при развитии остеомие- [17].…”
Section: пациенты и методыunclassified